Increased removal of nickel and organics in the upflow anaerobic sludge bed filter reactor using sulfate and sulfide additions - Jung, JY; Chung, YC; Ahn, DH (CHAPMAN HALL LTD, 1997)
Glucose (total organic carbon: 1,200 mg/l) and nickel (0 to 40 mg/l) were added to an anaerobic upflow sludge bed filter reactor. The removal efficiencies of total organic carbon and nickel were maintained to 95% and 98.5%, respectively, since nickel was precipitated with sulfide which was converted from sulfate added at 80 mg SO4-S/l by sulfate reducing bacteria. Sulfate therefore enhances its organic removal efficiency of AUBF reactor under the presence of heavy metal.